(untitled) (The Research of Medical Science Review, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by progressive damage to joint bones and cartilage, accompanied by persistent inflammation. RA significantly impacts patients’ quality of life by causing pain and functional limitations. Objective: The study aimed to investigate the association between functional limitations and pain intensity in patients with RA. Methods: A cross-sectional observational study was conducted over six months with 100 RA patients aged 35–50 years, selected through non-probability convenient sampling. Both male and female participants diagnosed with RA were included. Data were collected using the Health Assessment Questionnaire (HAQ) for functional disability and the Visual Analogue Scale (VAS) for pain intensity. Data analysis was performed using SPSS version 21, applying chi-square tests for statistical significance. Results: Pain intensity among the participants was distributed as follows: 19.8% reported mild pain, 61.4% moderate pain, and 17.8% severe pain. Regarding functional limitations, 18.8% reported no difficulty, 3.0% experienced some difficulty, 37.6% reported much difficulty, and 39.0% were unable to perform activities such as walking, reaching, gripping, hygiene, dressing, and grooming. Conclusion: The study highlights a significant association between functional limitations and pain intensity in RA patients. Functional impairment is common, with a considerable proportion of patients reporting moderate to severe pain and difficulty performing daily activities.